Experimental Study of Water Heating Efficiency between Aluminium and Copper Absorber Plate in Solar Flat Plate Collector - Billy, Anak Sup; Tanti Zanariah, Shamshir Ali; Mohd Farid, Zainudin; R. A., Bakar (Trans Tech Publications Inc., 2014)
Solar water heating using flat plate collector (FPC) is the widest application that had been used in residential and commercial area. The material for the absorber plate in FPC should have good thermal conductivity to ensure a high value for the heat removal yet able to store heat slightly high during minimum solar radiation period. An experimental of FPC water heating is conducted using copper and aluminium as absorber plate. The plates were exposed under intense sun radiation more than 800w/m2. The analysis is performed on the relationship between the material and the temperature difference of water. The results represented the heat gain and water heating efficiency between aluminium and copper. Aluminium had heat gain of 1100.69W. Copper had the heat gain of 1025.36W. The water heating efficiency calculated for aluminum is 0.97 while copper is 0.93. The paper finally justified that aluminium is better as the absorber plate in this flat plate solar collector compare to copper plate.